Analisis Laporan Penyusunan Keuangan Pada Koperasi Pegawai Wilayah Mandiri - Fauzan Habib; Muhammad Ikhsan Harahap (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The aim of this research is to find out how the North Sumatra Medan Independent Regional Employee Cooperative Center implements PSAK No. 27 in determining the elements and presenting financial statements so that the role of PSAK No. 27 as a standard used in carrying out cooperative functions and activities. The research was carried out in the form of a descriptive case study, namely one that describes the actual characteristics and conditions of a research object while the research is in progress. Data collection was carried out by means of observation, interviews and documentation. From the research results, it is known that in general PKP-RI has implemented PSAK No. 27 in presenting the financial statements, although in several cases there must be improvements in the presentation. This can be seen from the presentation of the cooperative’s financial reports. From the data obtained, it is known that the cooperative has prepared four of the five elements of a complete cooperative financial report, namely: Balance Sheet, Calculation of Business Results, Member Economic Promotion Report, and Notes to the Financial Report. Where cooperatives should also make Cash Flow Reports.